2015
DOI: 10.18378/rvads.v10i3.3699
|View full text |Cite
|
Sign up to set email alerts
|

Produção e avaliação da qualidade das barras de cereais elaborada com farinha de facheiro

Abstract: <p>As cactáceas constituem um importante elemento da paisagem, apresentando caules suculentos, cobertos por espinhos de diversas formas, tamanhos e dimensões, junto a outras espécies de cactáceas, formam a paisagem típica da região semiárida do Brasil. O facheiro é uma cactácea xerófila, robusta, pouco ramificada, de cor verde-escura, armada de espinhos agudos; com flores grandes isoladas e altas. A proposta do trabalho foi elaborar barras de cereais com farinhas da casca e da polpa do facheiro e determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
0
0
1
Order By: Relevance
“…Regarding the protein content, the formulations presented in this work had 12% and 11% (with and without treatment respectively), relatively higher and desirable contents, compared to similar products described in the literature, which presented 4.2% on average (Peuckert et al, 2010). As for the ash content, the cereal bars developed in this work had low levels in both formulations, however, these values are similar to those described by Deodato et al (2015) who reported levels of 2% in cereal bars elaborated with facheiro flour.…”
Section: Parametersupporting
confidence: 90%
“…Regarding the protein content, the formulations presented in this work had 12% and 11% (with and without treatment respectively), relatively higher and desirable contents, compared to similar products described in the literature, which presented 4.2% on average (Peuckert et al, 2010). As for the ash content, the cereal bars developed in this work had low levels in both formulations, however, these values are similar to those described by Deodato et al (2015) who reported levels of 2% in cereal bars elaborated with facheiro flour.…”
Section: Parametersupporting
confidence: 90%
“…As barras de cereais são classificadas como produto de confeitaria, com formato retangular, vendida em embalagens individuais, é um mercado que tem cada vez mais demonstrado crescimento (DEODATO et al, 2015). Para a elaboração de barras de cereal deve-se levar em consideração alguns fatores, como o tipo de cereal, o carboidrato apropriado, o enriquecimento com nutrientes e fibras, com a finalidade de otimizar o sabor e tempo de prateleira (GUTKOSKI et al, 2007).…”
Section: Uso De Farelo De Milho No Desenvolvimento De Novos Produtosunclassified